Metaverse as a stage in the development of the network society - Yi, Ren (Journal of the Belarusian State University. Journalism, 2023)
On the material of scientific articles by Belarusian, Russian and Chinese researchers, the stages of development of the concept of the metaverse are analysed, the features of its influence on the media industry are determined, and approaches to understanding the phenomenon of the metaverse are considered. Options for using new technologies in the media are proposed. It is shown that traditional media can use the non-fungible tokens (NFT) model to monetise content. It is demonstrated that new technologies affect the quality of perception of information by the audience and the popularity of TV programs. The possibilities of using virtual masters are described.